Enhancing Islamic Bank Performance: The Role Of Sharia Supervisory Board Attributes And Intellectual Capital - Rahmawati, Aryani Intan Endah; Prawestri, Adhelia Desi; Rosadi, Samsul; Wardani, Marita Kusuma (LPPM ISNJ Bengkalis, 2024)
Islamic banks are required to establish a sharia supervisory board (SSB). In that sense, there is a need to gain insight into whether the characteristics of the sharia supervisory board affect the performance of Islamic banks. This research investigates the effect of SSB size, sharia background, financial background, gender diversity, and the moderating effect of intellectual capital on the performance of Islamic banks in Indonesia, Malaysia, and Brunei Darussalam during 2011-2021. The data used in this study is taken from the annual reports of Islamic banks, as many as 269 observation data, and analyzed through the panel data regression. The results show that the financial background and gender diversity variables among SSBs impact the performance of Islamic banks in the countries. Theoretically, this study strengthens the relevance of resource dependence theory in Islamic banking by highlighting that more extensive and diverse boards attract expertise, networks, and legitimacy that support performance. Practically, this study can serve as a reference for practitioners and policymakers to underline the strategic importance of board composition, gender diversity, and intellectual capital investment as drivers of ethical compliance and financial stability.